Associations Between Early Childhood Parent–Child Attachment and Internalizing/Externalizing Symptoms: A Systematic Review and Narrative Synthesis. Issue 7 (3rd October 2021) - Badovinac, Shaylea D.; Pillai Riddell, Rebecca; Deneault, Audrey-Ann; Martin, Jodi; Bureau, Jean-François; O'Neill, Monica C.
Abstract: This systematic review aimed to provide a narrative synthesis of associations between the early childhood (i.e., preschool and early school age) attachment classification systems and internalizing and externalizing symptoms measured from preschool age through adolescence. The review was pre-registered with PROSPERO (#CRD42017073417) and followed PRISMA guidelines. Of the 9, 312 records screened, 34 articles comprising 15 samples were included in the review. Findings across studies suggest consistent associations between insecure early childhood attachment and both internalizing and externalizing symptoms during the preschool and school-age/middle childhood periods, with children classified as disorganized/controlling being at heightened risk. There is insufficient evidence to confirm associations with (pre)adolescent externalizing and internalizing symptoms. Future directions for research and clinical implications are discussed.